Functions of silicon and phytolith in higher plants - Rui Xu; Jianfeng Huang; Huijun Guo; Changming Wang; Hui Zhan (Plant Signaling & Behavior, 2023)
Silicon (Si) is abundant in the lithosphere, and previous studies have confirmed that silicon plays an important role in plant growth. Higher plants absorb soluble silicon from soil through roots which is deposited in plant tissues mainly in the form of phytoliths. Based on previous studies, the research progress in silicon and phytoliths in the structural protection, enhancement on photosynthesis and transpiration of plants and plant growth and stress resistance was reviewed. Meanwhile, gaps in phytolith research, including phytolith morphology and function, impact of diverse environmental factors coupling with phytoliths, phytolith characteristics at different stages of plant development and phytoliths in regional vegetation are identified. The paper intends to promote the wider application of phytolith research findings and provides reference for further research on phytoliths.